Integrating Chiropractic Care Into the Treatment of Migraine Headaches in a Tertiary Care Hospital: A Case Series. (March 2019) - Bernstein, Carolyn; Wayne, Peter M; Rist, Pamela M; Osypiuk, Kamila; Hernandez, Audrey; Kowalski, Matthew
This case series illustrates an integrated model of care for migraine that combines standard neurological care with chiropractic treatment. For each patient, we describe the rationale for referral, diagnosis by both the neurologist and chiropractor, the coordinated care plan, communication between the neurologist and chiropractor based on direct face-to-face "hallway" interaction, medical notes, team meetings, and clinical outcomes. Findings are evaluated within the broader context of the multicause nature of migraine and the impact of integrative chiropractic. Suggestions for future areas of research evaluating integrative approaches are discussed.